Association between mild or moderate obstructive sleep apnea-hypopnea syndrome and cognitive dysfunction in children - Zhao, Jing; Han, Shujing; Zhang, Jishui; Wang, Guixiang; Wang, Hua; Xu, Zhifei; Tai, Jun; Peng, Xiaoxia; Guo, Yongli; Liu, Haihong; Tian, Jinghong; Jin, Xin; et al. (Sleep medicine, 2018)
Childhood obstructive sleep apnea–hypopnea syndrome (OSAHS), the most common sleep-related breathing disorder, may lead to cognitive impairment. This study aims to investigate the association between mild or moderate childhood OSAHS and cognitive dysfunction. A total of 59 children (4–12 years of age) diagnosed with mild or moderate OSAHS by polysomnography and 60 age-  and sex-matched healthy children were included in the study. The China-Wechsler Younger Children Scale of Intelligence and China-Wechsler Intelligence Scale for Children were used to evaluate the cognition of the participating children aged <6 years and ≥6 years, respectively. In the <6-years-old subgroup, children with OSAHS had significantly lower scores of full-scale IQ (FIQ), verbal IQ (VIQ), comprehension test, and visual analysis than the healthy children (all p < 0.05). In the ≥6-years-old subgroup, VIQ and classification test scores were significantly lower in children with OSAHS than in the healthy controls (all p < 0.05). FIQ, VIQ, and performance IQ (PIQ) scores did not correlate with AHI, OAHI, and the lowest nocturnal SO2. Notably, in the <6-years-old subgroup of OSAHS, the accumulated time of SO2<90% (p = 0.046) and the percentage of the accumulated time of SO2<90% in the total sleep time (p = 0.034) correlated with PIQ negatively and significantly. Mild to moderate childhood OSAHS may adversely affect cognitive function, particularly in young children (<6 years of age). This study may increase the awareness of childhood OSAHS-associated cognitive dysfunction and advocate early interventions in childhood OSAHS. •Young children (<6 years) with OSAHS had lower scores of full scale and verbal IQ.•Young children with OSAHS performed less well in comprehension tests and visual analysis.•The accumulated time of SO2 <90% correlated with PIQ negatively in pediatric OSAHS.